Vocational Education at Special School in North Sumatra - Munawir Pasaribu; Rizka Harfiani (STAI Hubbulwathan Duri, 2021)
Vocational education is the proper treatment of work skills or life skills education, especially for students with special needs. This study aims to analyze the implementation of vocational education at A/B/C Melati 'Aisyiyah special school located in Tembung, North Sumatra Province, Indonesia. This study uses a qualitative approach, with field research type. The data collection is through observation, interview, and documentation, then analyzed with interactive analysis models, following the data validity test using triangulation methods. This study discovers that analyzing the vocational education implementation for special students at the high school level, namely from aspects: a) teacher potential, b) student potential, c) supporting infrastructure, d) vocational learning system and policy to grant students to work according to their ability, as one of the efforts to realize the school vision and mission. The implication of this study is to provide an overview of vocational education implementation for special students to have independence and responsibility in living their lives.